Literacia e inclusão digital no ensino superior online: impactos em adultos diplomados - Henriques, S.; Neves, C.; Silva, A. P.; Abrantes, P.; Ramos, M. R.; Jacquinet, M.; Backstrom, B.; Falé, I.; Magano, O. (Sociologia, Problemas e Práticas, 2023)
Based on a theoretical framework that mobilizes contributions from literacy and digital inclusion, lifelong learning, digital education and employability, the article provides an analysis of data collected from follow-up surveys of graduates who graduated between 2011 and 2018 through online higher education. The aim of this study is to contribute to deepening knowledge about digital skills and digital inclusion associated with adults who have graduated from courses offered under the digital education regime. The results inform public policy guidelines and corroborate the results of previous studies, regarding the positive impact of online education and training on digital literacy skills and digital inclusion levels. © 2023 Editora Mundos Sociais. All rights reserved.